Everyday Uses of Music Listening and Music Technologies by Caregivers and People With Dementia: Survey and Focus Group Study - Dianna Vidas; Romina Carrasco; Ryan M Kelly; Jenny Waycott; Jeanette Tamplin; Kate McMahon; Libby M Flynn; Phoebe A Stretton-Smith; Tanara Viera Sousa; Felicity A Baker (JMIR Publications, 2024)
BackgroundMusic has long been identified as a nonpharmacological tool that can provide benefits for people with dementia, and there is considerable interest in designing technologies to support the use of music in dementia care. However, to ensure that music technologies are appropriately designed for supporting caregivers and people living with dementia, there remains a need to better understand how music is currently used in everyday dementia care at home. ObjectiveThis study aims to understand how people living with dementia and their caregivers use music and music technologies in everyday caring, as well as the challenges they experience using music and technology. MethodsThis study used a mixed methods design. First, a survey was administered to 13 people living with dementia and 64 caregivers to understand their use of music and technology. Subsequently, 18 survey respondents (family caregivers: n=12, 67%; people living with dementia: n=6, 33%) participated in focus groups regarding their experiences of using music and technology in care. Interview transcripts were analyzed using reflexive thematic analysis. ResultsMost of the survey respondents (people living with dementia: 9/13, 69%; family caregivers: 47/63, 75%) reported using music often or very often in their daily lives. Participants reported a range of technologies used for listening to music, such as CDs, radio, and streaming services. Focus groups highlighted the benefits and challenges of using music and music technologies in everyday care. Participants identified using music and music technologies to regulate mood, provide joy, facilitate social interaction and connection, encourage reminiscence, provide continuity of music use before and after the dementia diagnosis, and make caregiving easier. The challenges of using music technology in everyday caring included difficulties with staying up to date with evolving technology and low self-efficacy with technology for people living with dementia. ConclusionsThis study shows that people with a dementia diagnosis and their caregivers already use music and music technologies to support their everyday care needs. The results suggest opportunities to design technologies that enable easier access to music and to support people living with dementia with recreational and therapeutic music listening as well as music-based activities.